Answer: A
Step-by-step explanation: 1+1+1+1-1=3 or you can think about it like this
1+1+1+1=4 then just subtract the negative to get 3
Answer:
13
Step-by-step explanation:
because 3+9=12+1=13
Are there any answer choice?
Answer:
Pierce has 16 coins
Ron has 40 coins.
Step-by-step explanation:
64÷4=16
64÷2=32+8=40
Factor theorem: if x-k is a factor of p(x), then p(k) = 0. The same can be said in reverse: if p(k) = 0, then x-k is a factor of p(x).
In this case, x-1 = x-k so k = 1. We'll plug this into f(x) below
f(x) = 14x^99 - 65x^56 + 51
f(1) = 14(1)^99 - 65(1)^56 + 51 ... replace every x with 1
f(1) = 14(1) - 65(1) + 51
f(1) = 14 - 65 + 51
f(1) = -51 + 51
f(1) = 0
The result is 0, so h(x) = (x-1) is a factor of f(x) = 14x^99-65x^56+51
-------------------
Answer: Choice A) yes